Eksplorasi Jamur Makroskopis Bukit Reli, Lubuklinggau Utara I, Sumatera Selatan - Yuni Krisnawati; Yunita Wardianti (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2026)
This study aimed to identify and describe the species of macroscopic fungi found in Bukit Reli, North Lubuklinggau District I. The method used was descriptive qualitative research through direct field observations and visual documentation of fungal specimens. Data were collected using exploratory surveys and morphological identification, then analyzed by matching specimen characteristics with scientific literature and fungal identification guides. The results showed that 47 species of macroscopic fungi were found in Bukit Reli, varying in color, shape, and growth substrate. Several species have potential as alternative food sources and ecological indicators of forest health. In conclusion, Bukit Reli has high diversity of macroscopic fungi and potential as supporting data for local conservation and learning resource development. Further research is recommended to investigate ecological functions, edibility potential, bioactive compounds, and seasonal variation in fungal diversity. Keywords: Biodiversity, Bukit Reli, Exploration, Macroscopic fungi, Species identification.